Health status of elderly bidayuh in singhai, Bau district, Sarawak - Welly, Francisca Emiliana (University Malaysia Sarawak, UNIMAS., 2010)
Ageing is said to be associated with decrease functional ability and also high prevalence of chronic medical condition which may affect the health status of the elderly and their quantity of life. This quantitative research is a descriptive study aimed to assess the health status and also the factors that influenced self-rated health of elderly Bidayuh living in Kampung Bobak and Kampung Sagah in Singhai zone.